Black-box modeling of nonlinear system using evolutionary neural NARX model - Nguyen Ngoc Son; Nguyen Duy Khanh; Tran Minh Chinh (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Nonlinear systems with uncertainty and disturbance are very difficult to model using mathematic approach. Therefore, a black-box modeling approach without any prior knowledge is necessary. There are some modeling approaches have been used to develop a black box model such as fuzzy logic, neural network, and evolution algorithms. In this paper, an evolutionary neural network by combining a neural network and a modified differential evolution algorithm is applied to model a nonlinear system. The feasibility and effectiveness of the proposed modeling are tested on a piezoelectric actuator SISO system and an experimental quadruple tank MIMO system.